2022
DOI: 10.3389/fmicb.2022.883122
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bacterial Diversity in Different Types of Daqu and Fermented Grains From Danquan Distillery

Abstract: Bacterial communities in high-temperature Daqu and fermented grains are important for brewing Jiang-flavor Baijiu such as Danquan Baijiu. Daqu is a saccharifying and fermenting agent, which has a significant impact on the flavor of Baijiu. However, bacterial communities in three different types of samples from the Danquan distillery (dqjq_ck, dqjqcp, and dqjp3) were still unclear, which limited further development of Danquan Baijiu. “dqjq_ck” and “dqjqcp” indicate high-temperature Daqu at days 45 and 135, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…In Daqu , as well as two types of PM cultures, 13 genera of AT bacteria were identified, including Thermoactinomyces , Limosilactobacillus , Kroppenstedtia , Weissella , etc., which dominated in DQ, while Bacillus and Aneurinibacillus shared in both MC and FC, and Lysinibacillus also dominated in the latter ( Figure 3 A). Kroppenstedtia , known for its high amylase and lipase secretion and organic acid metabolism [ 38 ], along with Bacillus , was highlighted as a functional bacteria in Daqu [ 39 ]. Aneurinibacillus , notable for its cellulose degradation of various enzymes, such as alkyl or aryl transferases, methyl transferases, and secretion abilities, was first detected in PM cultures, contributing to the formation of methyl esters [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Daqu , as well as two types of PM cultures, 13 genera of AT bacteria were identified, including Thermoactinomyces , Limosilactobacillus , Kroppenstedtia , Weissella , etc., which dominated in DQ, while Bacillus and Aneurinibacillus shared in both MC and FC, and Lysinibacillus also dominated in the latter ( Figure 3 A). Kroppenstedtia , known for its high amylase and lipase secretion and organic acid metabolism [ 38 ], along with Bacillus , was highlighted as a functional bacteria in Daqu [ 39 ]. Aneurinibacillus , notable for its cellulose degradation of various enzymes, such as alkyl or aryl transferases, methyl transferases, and secretion abilities, was first detected in PM cultures, contributing to the formation of methyl esters [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“… 57 Our previous study also found that with the higher HTD-making temperature, most yeasts and molds were destroyed, and the microbial community of HTD primarily propagated thermophilic bacteria such as Bacillus . 58 In addition, Bacillus was the dominant bacterium in sample “dqjqcp”. 58 Therefore, we suggested that Bacillus was primarily responsible for producing ethanol rather than yeast in the Danquan Baijiu production.…”
Section: Discussionmentioning
confidence: 99%
“… 58 In addition, Bacillus was the dominant bacterium in sample “dqjqcp”. 58 Therefore, we suggested that Bacillus was primarily responsible for producing ethanol rather than yeast in the Danquan Baijiu production. Therefore, we isolated the bacterial strain Bacillus sp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation